H. Gregg Lewis: Perhaps the Father of Modern Labor Economics - Daniel S. Hamermesh (Institute of Labor Economics (IZA), 2020)
H. Gregg Lewis did fundamental research outlining the economic effects of trade unions and considering how to measure them carefully. He also laid out the theory of the supply and demand for labor in careful detail that has underlain economists' thinking about these outcomes. Aside from innovating modern-style research in labor economics, his work provided an exemplar of care in thinking about and measuring economic phenomena. His study of labor markets foreshadowed numerous subsequent fundamental articles, including our theories of hedonic prices and of wage selectivity. Supervising numerous Chicago Ph.D. dissertations, all of which heavily bore his stamp and two of which were by future Nobel Prize winners, he contributed indirectly to the development of applied microeconomics through several later generations of researchers.
Keywords: B21; C29; 330; economics of unions; labor demand; labor supply; Chicago dissertations; general equilibrium; empirical methods